2017
DOI: 10.1080/08997659.2017.1360411
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Pathogenicity ofStreptococcus iniaein Cultured Red Hybrid Tilapia in Malaysia

Abstract: This study describes the isolation and pathogenicity of Streptococcus iniae in cultured red hybrid tilapia (Nile Tilapia Oreochromis niloticus × Mozambique Tilapia O. mossambicus) in Malaysia. The isolated gram-positive S. iniae appeared punctiform, transparently white, catalase and oxidase negative and produced complete β-hemolysis on blood agar, while a PCR assay resulted in the amplification of the 16 S rRNA gene and lactate oxidase encoded genes. The isolate was sensitive to tetracycline, vancomycin, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 21 publications
3
33
2
Order By: Relevance
“…Likewise, its capability to grow optimally in a medium with salt concentrations from 0% to 3.0% gave it an ability to be lethal to both freshwater and marine fish species (Kia and Mehrabi, 2013). Biochemical profiles of S. iniae HNM-1 differs with most of the previously reported strains, for instance, it exhibits great variations in ɑ-galactosidase, β-glucuronidase and trehalose reactions compared with the strains reported by (Rahmatullah et al, 2017;El Aamri et al, 2010;Jantrakajorn et al, 2014;Dodson et al, 1999), but comparable with the dolphin isolate which was the first isolated strain of S. iniae (Pier and Madin, 1976). Inconsistency in biochemical profiles is common among different strains of the bacteria, which can lead to frequent miss-identification of S. iniae using the biochemical method (Lau et al, 2003).…”
Section: O N L I N E F I R S T a R T I C L Econtrasting
confidence: 57%
See 1 more Smart Citation
“…Likewise, its capability to grow optimally in a medium with salt concentrations from 0% to 3.0% gave it an ability to be lethal to both freshwater and marine fish species (Kia and Mehrabi, 2013). Biochemical profiles of S. iniae HNM-1 differs with most of the previously reported strains, for instance, it exhibits great variations in ɑ-galactosidase, β-glucuronidase and trehalose reactions compared with the strains reported by (Rahmatullah et al, 2017;El Aamri et al, 2010;Jantrakajorn et al, 2014;Dodson et al, 1999), but comparable with the dolphin isolate which was the first isolated strain of S. iniae (Pier and Madin, 1976). Inconsistency in biochemical profiles is common among different strains of the bacteria, which can lead to frequent miss-identification of S. iniae using the biochemical method (Lau et al, 2003).…”
Section: O N L I N E F I R S T a R T I C L Econtrasting
confidence: 57%
“…S. iniae HNM-1 was found to be resistant to many important antibiotics that include Amoxicillin, gentamycin, Penicillin G and spectinomycin. This signifies an emergence of multidrug resistance strain unlike previously reported strains that were susceptible to most of the antibiotics (Rahmatullah et al, 2017;El Aamri et al, 2010;Kayansamruaj et al, 2017). The cumulative mortalities and LD 50 of HNM-1 strain in A. sinensis indicated the high vulnerability of A. sinensis to its infection.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 80%
“…Several researchers have demonstrated that the transmission of Streptococcus spp. in tilapia is horizontal (Iregui, Comas, Vasquez, & Verjan, ; Rahmatullah et al, ). Present studies have found high mortality and rates of bacterial infection with high stocking density (over 78 fish/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The isolated Gram-positive S. iniae appeared punctiform, transparently white, catalase and oxidase negative and produced complete b-hemolysis on blood agar. The isolate was sensitive to tetracycline, vancomycin, and bacitracin but was resistant to streptomycin, ampicillin, penicillin, and erythromycin (Ortega et al, 2018;Rahmatullah et al, 2017;Rajoo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%